2008
DOI: 10.1016/j.ygcen.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of matrix metalloproteinases during stimulated ovarian recrudescence in Siberian hamsters (Phodopus sungorus)

Abstract: The matrix metalloproteinases (MMPs) are a family of extracellular matrix-cleaving enzymes involved in ovarian remodeling. In many non-tropical species, including Siberian hamsters, ovarian remodeling is necessary for the functional changes associated with seasonal reproduction. We evaluated MMPs and their endogenous inhibitors (TIMPs), during photoperiod-induced ovarian recrudescence in Siberian hamsters. Hamsters were transferred from long-day (LD;16:8) to shortday (SD;8:16) photoperiods for 14wks, and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(66 citation statements)
references
References 50 publications
4
56
0
Order By: Relevance
“…This is the first study to date showing that avian granulosa cells are also capable of secreting gelatinolytic-active MMPs similar to mammalian species [45,50,53]. In the developing follicles, MMP9 protein was observed predominantly in granulosa cells in hamster [54], horse [50], and rhesus monkey [34]. However, in rat [45,55,56] and human [57], primarily theca-interstitial and perifollicular stroma cell enrichment of MMP9 was detected.…”
Section: Expression and Regulation Of Mmp3 In The Chicken Ovarymentioning
confidence: 73%
“…This is the first study to date showing that avian granulosa cells are also capable of secreting gelatinolytic-active MMPs similar to mammalian species [45,50,53]. In the developing follicles, MMP9 protein was observed predominantly in granulosa cells in hamster [54], horse [50], and rhesus monkey [34]. However, in rat [45,55,56] and human [57], primarily theca-interstitial and perifollicular stroma cell enrichment of MMP9 was detected.…”
Section: Expression and Regulation Of Mmp3 In The Chicken Ovarymentioning
confidence: 73%
“…Because typical ovarian function is reduced in regressed ovaries, it is likely that ovarian cells from a photore-gressed ovary respond differently to the cellular signals that characterize normal ovarian cyclicity when compared to cells in a functional ovary. Additionally, because the return to full ovarian function is not instantaneous, but rather a gradual process taking up to 8 weeks (Salverson et al, 2008), it may also be that photore-gressed ovaries respond differently to cellular signals in the early days or weeks of photostimulation as compared to response from these same cells later in recrudescence. Examining the effects of a more chronic MMP inhibition across multiple weeks of photostimulation will further our understanding of how MMP action contributes to resumption of ovarian function.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in GnRH subsequently reduces secretion of both luteinizing hormone (LH) and follicle-stimulating hormone (FSH), and the lack gonadotropin support effectively compromises both ovarian folliculogenesis and steroidogenesis (Schlatt et al, 1993). Exposure of adult, female Siberian hamsters to short photoperiods for 14 weeks reduces ovarian mass, estradiol concentrations, and both antral follicle and corpora lutea numbers (Moffatt-Blue et al, 2006), whereas transfer of photoregressed hamsters to LD for 2–8 weeks gradually restores normal reproductive activity (Salverson et al, 2008). This photostimulated ovarian recrudescence corresponds with differential expression of matrix metalloproteinases (MMPs; Salverson et al, 2008) and can be impeded with daily in vivo administration of pan-MMP inhibitor GM6001, as compared to non-treated or vehicle-treated (DMSO) controls (Whited et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we opted to supplement SD females with FSH only. Previous studies have shown that hypogonadotropism associated with SD is reversed upon transfer to LD, and ovarian recrudescence from the SD to LD phenotype is completed within w4 weeks (Anand et al 2002, Salverson et al 2008. Therefore, animals in all groups were killed after 4 weeks of treatment at 14 weeks of age.…”
Section: Experiments 1: Gonadotropin Suppression In Ldsmentioning
confidence: 99%